2'-Alkynylnucleotides: A Sequence- and Spin Label-Flexible Strategy for EPR Spectroscopy in DNA - Anderson, E; El-Sagheer, A; Porter, R; Brown, T; Haugland, M; Peña, J; Lovett, J (American Chemical Society, 2016)
Electron paramagnetic resonance (EPR) spectroscopy is a powerful method to elucidate molecular structure through the measurement of distances between conformationally well-defined spin labels. Here we report a sequence-flexible approach to the synthesis of double spin-labeled DNA duplexes, where 2′-alkynylnucleosides are incorporated at terminal and internal positions on complementary strands. Post-DNA synthesis copper-catalyzed azide–alkyne cycloaddition (CuAAC) reactions with a variety of spin labels enable the use of double electron–electron resonance experiments to measure a number of distances on the duplex, affording a high level of detailed structural information.